Fracture and Fatigue Assessments of Structural Components - Campagnolo, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In dealing with fracture and fatigue assessments of structural components, different approaches have been proposed in the literature. They are usually divided into three subgroups according to stress-based, strain-based, and energy-based criteria. Typical applications include both linear elastic and elastoplastic materials and plain and notched or cracked components under both static and fatigue loadings. The aim of this Special Issue is to provide an update to the state-of-the-art on these approaches. The topics addressed in this Special Issue are applications from nano- to full-scale complex and real structures and recent advanced criteria for fracture and fatigue predictions under complex loading conditions, such as multiaxial constant and variable amplitude fatigue loadings.